Analysis of Optimal Raw Material Inventory Needs in Small and Medium Industries (Study on Nadya Furniture in Ambon City) - La Irsan; Jusuf Sahupala; Tina D Kaisupy (Indo-Fintech Intellectuals: Journal of Economics and Business, 2021)
The purpose of this research is to determine the need for optimal raw material supplies at Nadya Furniture in Ambon City for a certain period of time, so that there is no delay in raw materials and production targets are set to be achieved. This type of research is qualitative research. The data sources used in this study are primary and secondary data. Data analysis tools used are demand forecasting with time series method and Material Requirement Planning (MRP). The results showed that the optimal order amount for ironwood was 96 meters for January and 396 meters for February, for linggua wood was 1,568 meters for January and 2,616 meters for February, and Linggua Board was 420 meters for January and 920 meters for February 2020. inventory costs for each raw material namely Ironwood Rp.3,139,744, Linggua Wood Rp.3,420,016, Hensel cabinet Rp.2.603.920, House lock Rp.1.965.768, cupboard handle Rp.1.965.760, Mirror Rp.1.765.600, Hensel door Rp.1.673.400 and Door handle Rp.2.874.528